Identificação e discriminação de resíduos de disparo de arma de fogo por fluorescência de raios x por reflexão total, espectrometria de massas com Ionização por paper spray e técnicas quimiométricas - Luisa Pereira e Ferreira (2020)
The determination of fired ammunition type by chemical analysis of gunshot residue (GSR), which is deposited on the hands of the shooter, is crucial to confirm or exclude a suspect as author of a crime. In this context, methods are proposed to identify and discriminate GSR from conventional and non-toxic ammunition (NTA) by Total Reflection X-Ray Fluorescence (TXRF), Paper Spray Mass Spectrometry (PS-MS), Principal Component Analysis (PCA) and Partial Least Square Discriminant Analysis (PLS-DA). The TXRF method proved to be adequate for identification of GSR inorganic components and for discrimination of the samples as a function of conventional ammunition caliber studied. The method efficiency was tested by comparing results obtained for real case samples by routine technique of Criminalistics Institute of Minas Gerais Civil Police, Graphite Furnace Atomic Absorption Spectroscopy (GFAAS), and also by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). There was coincidence of more than 90% between the sample classifications as positive or negative based on the limits practiced by the forensic laboratory, by the three techniques. A method for analyzing organic and inorganic gunshot residues (OGSR and IGSR, respectively) from a single sample collected with stubs was also developed. IGSR detection was accomplished with Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM-EDX) Scanning Electron Microscopy followed by detection and discrimination of OGSR by PS-MS associated with PLS-DA.